Sengketa Tanah, Kepastian Hukum, dan Dakwah Sosial: Merekonstruksi Keadilan Agraria melalui Yurisprudensi Sosiologi Islam - Ahmad Muhamad Musta’in Nasoha; Novia Eka Fitriyanti; Dyah Ayu Mawardah; Siti Fatimah Noviana Eka Ningrum; Itfifah Nurnailah Ramadhani; Hafitza Azzahra; Agatha Cahyani Setsetiahadi (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study examines the relationship between land disputes, legal certainty, and the role of social da’wah from an Islamic legal perspective in Indonesia. The increasing frequency of agrarian conflicts is not only driven by weaknesses in the land administration system, but also closely linked to social inequality and the limited integration of religious-based approaches in dispute resolution. These conditions highlight the need for a more holistic framework that combines legal, social, and moral dimensions in addressing land issues. This research employs a qualitative method using a descriptive-analytical literature review of relevant sources from Islamic law, national agrarian law, and socio-religious studies. The findings show that the principle of maslahah (public benefit) in Islamic law can serve as an ethical foundation for building a more just, humane, and sustainable agrarian legal system. In addition, social da’wah plays an essential role in increasing public legal awareness, strengthening moral responsibility, and acting as a mediator in community-based land conflicts. The study further proposes an integrated dispute resolution model that combines state law, Islamic law, and customary law to create more inclusive and effective solutions for agrarian conflicts in Indonesia.